Cultural tightness-looseness and national innovativeness: Impacts of tolerance and diversity of opinion - Carsten Deckert; Rahel Schomaker (Journal of Innovation and Entrepreneurship, 2022)
The links between innovativeness as a driver of economic performance, and the determinants of innovativeness have been investigated by management scholars and economists for decades, focusing mostly on "hard factors" as investment in research and development, or education. Focusing on a relatively neglected, but in times of globalization even more important aspect, the influence of cultural characteristics on innovativeness, we apply different econometric models to test for links between cultural tightness and looseness on the one hand, and national innovativeness on the other hand. We find that cultural tightness - in the sense of homogenous and intolerant societies - has a negative link to national innovativeness, while cultural looseness - in the sense of tolerant and diverse societies - displays a positive link to national innovativeness.
Keywords: 650; Culture; Diversity of opinion; Innovation; National innovativeness; Tolerance